2015
DOI: 10.1038/nrneph.2015.158
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and mediators of lung injury after acute kidney injury

Abstract: Acute kidney injury (AKI) is a common complication in hospitalized patients, associated with >50% mortality in those in intensive care who require renal replacement therapy. Data suggest that AKI is a systemic disease that adversely affects the immune system and organ function, and in this way contributes to the high mortality observed in affected patients. Data from patients and animal models indicate that AKI adversely affects the lungs. Respiratory complications are common in patients with AKI and include p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 137 publications
4
118
0
6
Order By: Relevance
“…AKI-mediated lung injury is well described in animal models and is predominantly characterized by lung inflammation, as judged by increased cytokines, chemokines, and neutrophils by 4 hours post-AKI 12 . Non-cardiogenic pulmonary edema is variably present 12 . By 24 hours, T cell infiltration, necroptosis, parthanatos, apoptosis, and increased caspase-3 activity are present 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…AKI-mediated lung injury is well described in animal models and is predominantly characterized by lung inflammation, as judged by increased cytokines, chemokines, and neutrophils by 4 hours post-AKI 12 . Non-cardiogenic pulmonary edema is variably present 12 . By 24 hours, T cell infiltration, necroptosis, parthanatos, apoptosis, and increased caspase-3 activity are present 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Circulating cytokines may have deleterious effects on other organs and higher levels have been shown to be associated with adverse clinical outcomes, including prolonged duration of mechanical ventilation, intensive care and hospital length of stay [26, 40, 41]. IL-8 is a potent neutrophil cytokine that promotes lung neutrophil accumulation and lung tissue injury [42]. Liu et al demonstrated that serum IL-6 and IL-8 are predictive of AKI and prolonged duration of mechanical ventilation in children following cardiac surgery [30].…”
Section: Discussionmentioning
confidence: 99%
“…Data also support that after the initial 24 hours of critical illness, the maintenance of a net even fluid balance is important. 26 On the other hand, tubular epithelial cells may directly contribute to the production of inflammatory mediators that may propagate the injury locally or in distant organs. 7,23 Pulmonary congestion and oedema may also occur without fluid overload in patients with AKI.…”
Section: Husain-syed Et Almentioning
confidence: 99%
“…7,23 Pulmonary congestion and oedema may also occur without fluid overload in patients with AKI. 26,30 In addition, animal models have demonstrated that during AKI, the integrity of the alveolar-capillary barrier is impaired by various factors, which causes fluid accumulation in the lung. Recent findings indicate a direct interaction between the lung and kidney.…”
Section: Husain-syed Et Almentioning
confidence: 99%